Effcacy of a Self-Management Programme in Breast Cancer Patients - Soivong, Pratum; Sawasdisingha, Piyawan; Tanvattanagul, Chiragul; Fukul, Arporn; Kaewinta, Yupawon; Puangsaijai, Sureerat; Wannavongs, Gulyarath (Journal of Thailand Nursing and Midwifery Council, 2018)
Objective: To examine, based on Roger’s theory of innovation diffusion, the effcacy of a self-management programme in breast cancer patients treated at a university hospital and a cancer hospital. Design: Operational study. Methodology: The study was conducted in 5 successive stages: 1) the education stage; 2) the persuasion stage; 3) the decision stage; 4) the operation stage; and 5) the confrmation stage. The participants were 2 groups of breast cancer patients. The frst group consisted of 121 patients, 75 having received treatment prior to the administration of the programme and the other 46 being treated during the administration of the programme. The second group consisted of 17 registered nurses. The data were analysed based on frequency, percentage and content analysis. Results: A high percentage of the patients who participated in the programme displayed good self-management behaviour, good quality of life, moderate level of anxiety, and no sign of depression, compared with those who did not. The registered nurses who employed this programme considered it to be practical and have higher caregiving effcacy. However, the large number of patients receiving chemotherapy each day was identifed as the main hindrance to the administration of this programme to every patient. Recommendations: It is recommended that this programme be integrated with standard care, and that multimedia materials be developed to educate patients on the disease, therapy, and self-management during chemotherapy. This could enable nurses in charge to promote self-management in response to each patient’s problem and to cope with the large number of breast cancer patients receiving chemotherapy on a daily basis